Parasitism by argulids (Crustacea: Branchiura) in piranhas (Osteichthyes: Serrasalmidae) captured in the Caiçara bays, upper Paraguay River, Pantanal, Mato Grosso State, Brazil - Fontana, Márcio; Takemoto, R. M.; Malta, José C.O.; Mateus, L. A.F. (Neotropical Ichthyology, 2012)
In this study, 446 fishes were analyzed: 190 Pygocentrus nattereri, 193 Serrasalmus maculatus, and 63 S. marginatus.They were captured in two bays, upper and lower Caiçara, in the upper Paraguay River basin, during one hydrological cycle from May 2008 to April 2009. Six species of Branchiura were found: Dolops bidentata, D. longicauda, Dolops sp., Argulus multicolor, A. chicomendesi, and Dipteropeltis hirundo. All fish species were infested by more than one species of Branchiura and the overall prevalence was 33.4%. The following prevalences were observed: 52.6% in P. nattereri; 20.3% in S. maculatus, and 15.8% in S. marginatus. The relative condition factor (Kn) differed significantly between parasitized and non parasitized individuals only in P. nattereri and S. maculatus. There was no correlation between Kn and abundance of parasites nor between body length (Ls) and intensity of infestation, in all three host species. © 2012 Sociedade Brasileira de Ictiologia.
Keywords: Argulidae; Argulus; Branchiura (crustacea); Characiformes; Crustacea; Dipteropeltis Hirundo; Osteichthyes; Pisces; Pygocentrus; Pygocentrus Nattereri; Serrasalmidae; Serrasalmus; Serrasalmus Marginatus